A Systematic Review on Cover Selection Methods For Steganography: Trend Analysis, Novel Classification and Analysis of the Elements - Muhammad Harith Noor Azam; Farida Hazwani Mohd Ridzuan; M. Norazizi Sham Mohd Sayuti; A H Azni; Nur Hafiza Zakaria; Vidyasagar Potdar (Elsevier, 2026)
Indexed by WOS/ Scopus